2023
DOI: 10.1002/nbm.5084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clamping end‐tidal CO2 on neurofluidic low‐frequency oscillations

Brianna Kish,
J. Jean Chen,
Yunjie Tong

Abstract: In recent years, low‐frequency oscillations (LFOs) (0.01–0.1 Hz) have been a subject of interest in resting‐state functional magnetic resonance imaging research. They are believed to have many possible driving mechanisms, from both regional and global sources. Internal fluctuations in the partial pressure of CO2 (PCO2) has long been thought of as one of these major driving forces, but its exact contributions compared with other mechanisms have yet to be fully understood. This study examined the effects of end‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Further, global BOLD signals are similarly present in both conditions, as reflected in the explained variance estimates of the first principal component between the two conditions (PC1 free r 2 = 0.28; PC1 clamped r 2 = 0.25; Supplementary Figure 10). Consistent with a previous report comparing overall time-lag structure of BOLD signals between clamped and free breathing conditions (Kish et al, 2023), we found that the spatiotemporal structure of global BOLD signals was similarity maintained in clamped CO2 conditions (Supplementary Figure 4).…”
Section: Global Bold Signals Under Clamped Co2 Conditionssupporting
confidence: 92%
“…Further, global BOLD signals are similarly present in both conditions, as reflected in the explained variance estimates of the first principal component between the two conditions (PC1 free r 2 = 0.28; PC1 clamped r 2 = 0.25; Supplementary Figure 10). Consistent with a previous report comparing overall time-lag structure of BOLD signals between clamped and free breathing conditions (Kish et al, 2023), we found that the spatiotemporal structure of global BOLD signals was similarity maintained in clamped CO2 conditions (Supplementary Figure 4).…”
Section: Global Bold Signals Under Clamped Co2 Conditionssupporting
confidence: 92%